The Creativity Level in Writing Mini Fiction Based on Ecopreneurship through Design Thinking in Online Learning - Sani Aryanto; Tatat Hartati; Bunyamin Maftuh; Deni Darmawan; Juppri Bacotang (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
The aim of this research is to determine the effect of the design thinking approach assisted by synchronous media Zoom and asynchronous media Google Classroom on writing skills for mini fiction based on ecopreneurship in terms of the creativity level (low, medium, and high). Method of research used was quasi-experimental method with  3 x 2 factorial design and involving 60 students from the Elementary School Teacher Education Study Program as samples in Universitas Islam 45 Kota Bekasi, Universitas Pendidikan Indonesia, and Universitas Kristen Indonesia Toraja. The results of research prove that there is an interaction effect between learning using the design thinking approach assisted by synchronous media Zoom and asynchronous media GCR with levels of creativity together towards improving writing skills for mini fiction based on ecopreneurship with a sig. (0.004) < α (0.05). which has implications for increasing the quantity and quality of innovative learning approaches in elementary education Keywords: Writing Mini Fiction, Entrepreneurship, Design Thinking